The Role of Gender for Teachers’ Reactions to Social Exclusion Among Students - Beißert, Hanna; Staat, Miriam; Bonefeld, Meike (Frontiers in Education, 2022)
Social exclusion, i.e., being kept apart from others and not being allowed to join, is a common phenomenon at school and can have severe consequences for students’ healthy development and success at school. This study examined teachers’ reactions to social exclusion among students focusing on the role of gender. Specifically, we were interested in potential effects of gender-specific socialization and social expectations linked to gender for teachers’ reactions to social exclusion among students. We used hypothetical scenarios in which a student is being excluded from a study group by other students. We focused on the gender of the teacher (as an observer of exclusion) on the one hand and on the gender of the excluded student on the other hand. In the hypothetical scenarios, we varied the gender of the excluded student by using either a typical female or male name. The study included 101 teachers from different school tracks in Germany (Mage = 36.93, SD = 9.84; 84 females, 17 males). We assessed teachers’ evaluations of the exclusion scenario and their anticipated reactions, i.e., how likely they were to intervene in such a situation and what they would specifically do. As expected, the participating teachers showed a general tendency to reject exclusion among students. This tendency was even more pronounced among female teachers compared to male teachers. Interestingly, these gender differences on the attitudinal side did not translate into differences in teachers’ behavioral intentions: for the likelihood to intervene, we did not find any differences based on the gender of the teacher. In terms of the gender of the excluded student, things were different: The gender of the excluded student did not affect teachers’ evaluations of the exclusion scenario. Yet, the gender of the excluded was relevant for participants’ behavioral intentions. Namely, teachers were less likely to intervene in the scenario if a boy was excluded. These findings are in line with considerations related to gender-specific socialization and social expectations linked to gender. Overall, the study demonstrates that gender is an important aspect in the context of social exclusion and further research should explicitly focus on how socialization and gender expectations can explain these findings.